ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM FILM BUMI TADULAKO KARYA PUSDATIN - Wafak Fatkul Nuli; Ika Ari Pratiwi; Sekar Dwi Ardianti (Journal Prakarsa Paedagogia, 2022)
This study aims to describe the analysis of character education values in the film Bumi Tadulako by Pustadin. This study uses qualitative research with a critical discourse analysis method approach. Data collection is done by observation, interviews, documentation. The research was conducted at SDN Wegil Sukolilo Pati. The object of research is the values of character education in films in Civics learning in elementary schools, where the fourth grade teacher is the facilitator and the research subject is the fourth grade student informant consisting of 6 students, 3 boys and 3 girls. The data analysis used by the discourse analysis technique focuses on two elements, namely, first, at the word level and second, how the events and actors involved in an event are about to be discussed. The results showed that there were values of character education in the film "Bumi Tadulako" by Pusdatin, namely Religion, Nationalism, Mandiri and Mutual Cooperation. The implementation of character education values in Civics learning through the film Bumi Tadulako has been implemented and has been carried out, namely praying before the Civics learning begins, flag ceremony on Mondays, doing assignments for Civics subjects themselves, and cleaning the classroom when finished learning PPKn.